2012
DOI: 10.1111/j.1365-2966.2011.20303.x
|View full text |Cite
|
Sign up to set email alerts
|

The LABOCA survey of the Extended Chandra Deep Field-South: clustering of submillimetre galaxies

Abstract: Field-South : clustering of submillimetre galaxies.', Monthly notices of the Royal Astronomical Society., 421(1). pp. 284-295. Further information on publisher's website: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
216
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 164 publications
(250 citation statements)
references
References 158 publications
33
216
1
Order By: Relevance
“…To some degree, this phenomena was expected from early radio studies (e.g. Pope et al, 2006;Ivison et al, 2007), clustering measurements Hickox et al, 2012), and numerical models . We note that not all high-resolution studies of SMGs have revealed multiplicity to the same extent as the Hodge et al (2013b) and Karim et al (2013) which could be biased due to the known underdensity of bright SMGs in the Chandra Deep Field South.…”
Section: Dsfg Multiplicitymentioning
confidence: 99%
See 4 more Smart Citations
“…To some degree, this phenomena was expected from early radio studies (e.g. Pope et al, 2006;Ivison et al, 2007), clustering measurements Hickox et al, 2012), and numerical models . We note that not all high-resolution studies of SMGs have revealed multiplicity to the same extent as the Hodge et al (2013b) and Karim et al (2013) which could be biased due to the known underdensity of bright SMGs in the Chandra Deep Field South.…”
Section: Dsfg Multiplicitymentioning
confidence: 99%
“…This evolution suggests that the SMGs are likely to evolve into luminous elliptical galaxies in the local Universe. The figure is reproduced with permission from Hickox et al (2012).…”
Section: Clustering Of Dsfgsmentioning
confidence: 99%
See 3 more Smart Citations